Emerging Markets from a Multidisciplinary Perspective Challenges, Opportunities and Research Agenda (Advances in Theory and Practice of Emerging Markets,, 2018)
This book examines prominent issues in the Emerging Markets (EM) from a variety of disciplines in order to make useful societal contributions through knowledge exchange. EMs offer enormous opportunities, but realizing them is both challenging and risky due to inherent uncertainties of such markets. EM's also have unique characteristics that makes them different from developed countries. This causes implications for both theory and practice. These markets necessitate substantial adaptations of developed theories and approaches employed in the Western world. This book investigates problems specific to emerging markets, and identifies new theoretical constructs, hypotheses (re)development, and emphasizes institutional contexts. The chapters in this book establish new conceptual and theoretical paradigms from multidisciplinary perspectives concentrated in the areas of information systems, electronic government, and digital and social media matters. The book focuses on topics in these areas such as digital enterprises, sustainability, telemedicine, and Information Communication Technology (ICT) and surveys the potential challenges and opportunities that may arise. These concepts and topics covered in this book are vital for making the global economy more equitable and sustainable. .